2007
DOI: 10.1016/j.molimm.2007.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKCδ in IFN-γ-inducible CIITA gene expression☆

Abstract: The class II transactivator (CIITA) is a key regulatory factor for MHC class II expression. Here, we demonstrate that PKCδ plays an important role in regulating IFN-γ-inducible CIITA gene expression in macrophages. Inhibition of PKCδ by either a PKCδ inhibitor or a dominant negative (DN) mutant form of PKCδ led to down-regulation of CIITA expression. The decrease in CIITA expression by PKCδ inhibition was in part due to the reduced recruitment of serine 727-phosphorylated Stat1 and histone acetyltransferases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Because Rho family GTPases are involved in a variety of immune responses as well as cellular functions, statin-mediated inhibition of Rho family GTPases' function provides a better understanding of the molecular mechanisms and diverse actions of statins. Other signaling pathways such as activation of PKCδ, PKCα and PKCβII have been implicated in CIITA gene expression [41, 42]. It will be of interest to determine if statins influence these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Because Rho family GTPases are involved in a variety of immune responses as well as cellular functions, statin-mediated inhibition of Rho family GTPases' function provides a better understanding of the molecular mechanisms and diverse actions of statins. Other signaling pathways such as activation of PKCδ, PKCα and PKCβII have been implicated in CIITA gene expression [41, 42]. It will be of interest to determine if statins influence these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence has shown that the activity of CIITA is tightly regulated at multiple levels, including expression, GTP binding, dimerization, nuclear translocation, and phosphorylation (42,(61)(62)(63)(64)(65), whereas the intracellular signaling pathways involved in CIITA regulation, namely phosphorylation, are only starting to emerge. Although several kinases have been identified as mediators of CIITA expression and function, their respective roles differ, reflecting a complex regulatory mechanism alternatively capable of activating or inhibiting CIITA function.…”
Section: Discussionmentioning
confidence: 99%
“…In the Type II IFN system five different serine kinases for the transactivation domain (TAD) of Stat1/phosphorylation on serine 727 have been demonstrated in different cell systems. These include PKCδ (30, 31), calmodulin dependent kinase II (CAMKII) (32), PKCε (33), PKCα (34), Erk (35) and cyclin dependent kinase 8 (CDK8) (36) (Table 2). Thus, it appears that in the Type I IFN system, PKCδ is the predominant kinase that regulates phosphorylation of Stat1 on serine 727 (Table 2), while in the Type II IFN system several serine kinases appear to play roles in different cell types (Table 2).…”
Section: Jak-stat Pathwaysmentioning
confidence: 99%
“…SOCS1 targeting by miR-122 in liver Huh7 cells significantly increases type I IFN expression (109). miR-29 targets IFNγ mRNA and the transcription factors T-bet and Eomes, inhibiting IFNγ production (130, 31). Additionally, using miR databases, at least 17 miRs have been identified that potentially target IFNγ, including miR-29 (132).…”
Section: Micrornas (Mirs) and The Ifn Responsementioning
confidence: 99%